Emergency Departments' Uptake of Telehealth for Stroke Versus Pediatric Care: Observational Study - Kori S Zachrison; Emily M Hayden; Krislyn M Boggs; Tehnaz P Boyle; Jingya Gao; Margaret E Samuels-Kalow; James P Marcin; Carlos A Camargo Jr (JMIR Publications, 2022)
BackgroundTelehealth for emergency stroke care delivery (telestroke) has had widespread adoption, enabling many hospitals to obtain stroke center certification. Telehealth for pediatric emergency care has been less widely adopted. ObjectiveOur primary objective was to determine whether differences in policy or certification requirements contributed to differential uptake of telestroke versus pediatric telehealth. We hypothesized that differences in financial incentives, based on differences in patient volume, prehospital routing policy, and certification requirements, contributed to differential emergency department (ED) adoption of telestroke versus pediatric telehealth. MethodsWe used the 2016 National Emergency Department Inventory-USA to identify EDs that were using telestroke and pediatric telehealth services. We surveyed all EDs using pediatric telehealth services (n=339) and a convenience sample of the 1758 EDs with telestroke services (n=366). The surveys characterized ED staffing, transfer patterns, reasons for adoption, and frequency of use. We used bivariate comparisons to examine differences in reasons for adoption and use between EDs with only telestroke services, only pediatric telehealth services, or both. ResultsOf the 442 EDs surveyed, 378 (85.5%) indicated use of telestroke, pediatric telehealth, or both. EDs with both services were smaller in bed size, volume, and ED attending coverage than those with only telestroke services or only pediatric telehealth services. EDs with telestroke services reported more frequent use, overall, than EDs with pediatric telehealth services: 14.1% (45/320) of EDs with telestroke services reported weekly use versus 2.9% (8/272) of EDs with pediatric telehealth services (P<.001). In addition, 37 out of 272 (13.6%) EDs with pediatric telehealth services reported no consults in the past year. Across applications, the most frequently selected reason for adoption was "improving level of clinical care." Policy-related reasons (ie, for compliance with outside certification or standards or for improving ED performance on quality metrics) were rarely indicated as the most important, but these reasons were indicated slightly more often for telestroke adoption (12/320, 3.8%) than for pediatric telehealth adoption (1/272, 0.4%; P=.003). ConclusionsIn 2016, more US EDs had telestroke services than pediatric telehealth services; among EDs with the technology, consults were more frequently made for stroke than for pediatric patients. The most frequently indicated reason for adoption among all EDs was related to clinical care.